Pensamiento indígena y planes de estudio en políticas públicas: ¿es posible una descolonización epistémica desde las universidades mexicanas? - De la Cruz Rojas, Edgar Andrés (2025)
In Latin America, various voices have questioned the role of universities in reproducing hegemonic epistemic structures. This article analyzes how five undergraduate programs in public policy, offered by Mexican public universities, incorporate—and to what extent—elements of Indigenous thought into their curricula as part of a possible curricular transformation that challenges the coloniality of knowledge. An analytical matrix based on four dimensions (epistemic, ontological, organizational, and political-ethical) was applied to evaluate the curricular designs through document analysis. The findings reveal limited incorporation, generally superficial or fragmented, with only one program showing significant progress in the organizational dimension. The study concludes that, although there are incipient efforts, most programs have yet to structurally integrate Indigenous epistemological and ontological frameworks that foster a dialogue of knowledges and challenge modern-colonial knowledge systems.